2001
DOI: 10.1038/labinvest.3780232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Alterations of Barrett's Esophagus on Microdissected Endoscopic Biopsies

Abstract: SUMMARY:Alterations in proto-oncogenes and tumor suppressor genes play a role in the sequence from Barrett's metaplasia to esophageal adenocarcinoma. The present study aims to ascertain whether molecular abnormalities take place in Barrett's metaplasia and low-grade dysplasia and to correlate them with the histological features of the esophageal mucosa. Forty-one formalin-fixed, paraffin-embedded endoscopic esophageal biopsies were classified according to the type of metaplastic changes (noncolumnar fundic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…These findings support the notion that two different pathways lead to adenocarcinomas of the distal esophagus and esophagogastric junction: one in which intestinal-type epithelium with goblet cells becomes dysplastic (intestinal pathway) and another in which dysplasia arises in cardiac-type glandular mucosa (non-intestinal pathway). [39][40][41] In contrast, an alternative explanation for the lack of intestinal metaplasia in some adenocarcinomas, 39 overgrowth of short segment intestinal metaplasia by large tumors, 17,42 explains neither the absence of intestinal-type mucosa in certain small esophageal adenocarcinomas 43 nor our observation of phenotypic and molecular differences. Thus, adenocarcinomas of the distal esophagus and esophagogastric junction may be stratified based on the presence or absence of background Barrett mucosa, with unique clinicopathological characteristics in either group, but without significant survival differences.…”
Section: Discussionmentioning
confidence: 58%
“…These findings support the notion that two different pathways lead to adenocarcinomas of the distal esophagus and esophagogastric junction: one in which intestinal-type epithelium with goblet cells becomes dysplastic (intestinal pathway) and another in which dysplasia arises in cardiac-type glandular mucosa (non-intestinal pathway). [39][40][41] In contrast, an alternative explanation for the lack of intestinal metaplasia in some adenocarcinomas, 39 overgrowth of short segment intestinal metaplasia by large tumors, 17,42 explains neither the absence of intestinal-type mucosa in certain small esophageal adenocarcinomas 43 nor our observation of phenotypic and molecular differences. Thus, adenocarcinomas of the distal esophagus and esophagogastric junction may be stratified based on the presence or absence of background Barrett mucosa, with unique clinicopathological characteristics in either group, but without significant survival differences.…”
Section: Discussionmentioning
confidence: 58%
“…Up to now, only a few reports have investigated the genetic alterations comprising MSI and LOH in BE patients, indicating that genetic alterations take place earlier in the development of SIM. 37,38 We previously found that GIN in SIM and gastric intestinal metaplasia may be associated with BE 39 and gastric carcinogenesis, 31,33 respectively. There have so far been very few reports regarding the alteration of E-cadherin in BE and EAC, [40][41][42] and loss of or reduced E-cadherin expression is considered to play a role in the progression of BE to EAC.…”
Section: Discussionmentioning
confidence: 99%
“…According to previously described methods [5,6], normal and tumor tissues were microdissected under direct light microscopy and digested overnight in a lysis buffer with 5% proteinase K. The DNA was directly tested for BAT25, BAT26, D2S123, D5S346, D17S250, D17S513, and TP53 microsatellites in a silver-stained 9% polyacrylamide gel. Loss of heterozygosity (LOH) was detected if one of the tumor bands decreased 30% below the corresponding normal band intensity.…”
Section: Methodsmentioning
confidence: 99%